PENILAIAN PERFORMA DAUN DAN TAJUK Cosmos sulphureus Cav. TERHADAP PEMUPUKAN ORGANIK DAN ANORGANIK - Ray March Syahadat; Ismail Saleh (Universitas Gunadarma, 2020)
Cosmos sulphureus Cav. Known as a horticultural plant that has many benefits. Several studies reported its benefits as a vegetable plant, natural coloring, biopesticide, apiary, therapeutic plant, and ornamental plants. Research on its function as a landscape plant is still rarely studied. Though this plant has a characteristic of growth that is different from other types of cosmos/kenikir. This study aims to assess the appearance of leaves and canopy of C. sulphureus plants as landscape plant in organic and inorganic fertilizing. The analytical methods used in this study were chi-square, Kendall's W test, scenic beauty estimation, semantic differential, and paired comparison. The results shows fertilized of C. sulphureus leaf and canopy appearance significantly differ than not fertilized C. sulphureus. Fertilization with organic fertilizer shows the preferred results by 36 respondents because it has impression of height on its appearance.